Appeal and attitude : prospects for ultimate meaning - Smith, Steven G. (Indiana series in the philosophy of religion., 2005)
In Appeal and Attitude, the author offers a multicultural view into issues at the heart of existentialism, hermeneutics, and the phenomenology of religion. By looking closely at the concepts of appeal, or what commands our attention, and attitude, or the quality of the attention we pay, Smith probes into the core of religious ideals to answer questions such as why faith and rationality are compelling and how religious experience becomes meaningful.